Agarose stamped method: a simple and customizable immobilization technique for zebrafish larvae - Jutoy, John; Mehrabi, Hossein; Bansal, Pushkar; Jung, Erica E. (Frontiers in Behavioral Neuroscience, 2025)
Standardized immobilization of zebrafish larvae is crucial for consistent behavioral assays such as optokinetic response, feeding, and tail-movement analyses, but traditional agarose embedding methods remain labor-intensive and variable. We developed the Agarose Stamped Device (ASD), a low-cost platform that imprints larva-sized wells into agarose, enabling rapid and reproducible alignment of multiple larvae while preserving viability. Customizable designs permit immobilization while maintaining eye, mouth, or tail freedom—achieved far more easily than with traditional embedding and post-processing. We demonstrate that the ASD sufficiently stabilizes larvae for high-resolution eye tracking, feeding assays, and tail-movement analyses. By combining standardized positioning with behavioral flexibility, the ASD broadens the range of feasible zebrafish experiments and lowers barriers to high-throughput behavioral neuroscience.